2019
DOI: 10.1002/aur.2156
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of voice control related to prosody in autism spectrum disorder and first‐degree relatives

Abstract: Differences in prosody (e.g., intonation, rhythm) are among the most obvious language‐related impairments in autism spectrum disorder (ASD), and significantly impact communication. Subtle prosodic differences have also been identified in a subset of clinically unaffected first‐degree relatives of individuals with ASD, and may reflect genetic liability to ASD. This study investigated the neural basis of prosodic differences in ASD and first‐degree relatives through analysis of feedforward and feedback control i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 77 publications
3
21
1
1
Order By: Relevance
“…Given that pragmatic impairment is a de ning feature of ASD (1)(2)(3)(4)(5), and subclinical pragmatic language differences have been repeatedly documented in ASD relatives (12,(16)(17)(18)20), associations between pragmatics and neural processing of speech sounds are signi cant in implicating FFR as neural mechanism related to a core symptom domain in ASD. Associations between response latencies and key pragmatic language skills in parents are also intriguing in suggesting that even subtle differences in neural processing of sound might have reverberating effects on downstream, more complex language abilities, such as pragmatics, which rely on the integration of many foundational mechanisms and skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that pragmatic impairment is a de ning feature of ASD (1)(2)(3)(4)(5), and subclinical pragmatic language differences have been repeatedly documented in ASD relatives (12,(16)(17)(18)20), associations between pragmatics and neural processing of speech sounds are signi cant in implicating FFR as neural mechanism related to a core symptom domain in ASD. Associations between response latencies and key pragmatic language skills in parents are also intriguing in suggesting that even subtle differences in neural processing of sound might have reverberating effects on downstream, more complex language abilities, such as pragmatics, which rely on the integration of many foundational mechanisms and skills.…”
Section: Discussionmentioning
confidence: 99%
“…Given repeated observations that parents of individuals with ASD may display subclinical pragmatic language differences (16,17,20), and speci cally in neural mechanisms contributing to audio-vocal integration impacting prosody (12), we predicted that the ASD parent group would display increased neural response latencies and reduced delity of neural pitch compared to parent controls. We predicted that atypicalities in FFR would relate to pragmatic and prosodic abilities in individuals with ASD and their parents, and that parent-child associations would emerge in the delity of neural response to speech sounds, which would support FFR as a potential heritable neural marker of language-related impairments in ASD.…”
mentioning
confidence: 99%
“…Auditory feedback control of speech in autistic children and adults, and their first-degree relatives, has also been examined by Patel et al [2019]. In this study, when exposed to FAF perturbations, larger compensatory vocal responses were produced by both autistic individuals and their first-degree relatives, relative to age-matched control groups.…”
Section: Discussionmentioning
confidence: 83%
“…The results of this study indicated that children with 16p11.2 deletions produced larger magnitude responses relative to siblings without the 16p11.2 deletion ( n = 4) and neurotypical comparisons ( n = 5). More recently, Patel, Kim, Larson, and Losh [2019] also examined responses to FAF in a sample ( n = 17) of autistic children and adults between the ages of 9 and 32 years. The results indicated that autistic participants produced larger vocal responses to the FAF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation